Germline targeted next-generation sequencing in patients with adrenal incidentalomas - Messina, Erika; Inglesi, Alessia; Puglisi, Soraya; Barač Nekić, Anja; Morelli, Valentina; Alessi, Ylenia; Zibar Tomsic, Karin; Palmieri, Serena; Tomaiuolo, Pasquale; Grosso, Enrico; Ferraù, Francesco; Chiodini, Iacopo; et al. (Frontiers in Endocrinology, 2025)
ObjectiveAdrenal incidentalomas are commonly detected in clinical practice. Despite growing interest in their molecular features, their germline genetic background remains largely unexplored. This study investigated the presence and potential pathogenic role of germline variants (GVs) in these patients using a targeted next-generation sequencing (NGS) approach, and explored possible genotype-phenotype correlations.DesignThis multicenter retrospective study included 191 patients with incidentally discovered adrenal masses from four European reference centers. Patients with adrenocortical carcinoma, pheochromocytoma and primary aldosteronism were excluded.MethodsGermline DNA was extracted from peripheral blood and analyzed using a custom next-generation sequencing (NGS) panel targeting 21 genes potentially involved in adrenal tumorigenesis. Bioinformatic analysis was followed by variant classification using the ClinVar and VarSome databases, in accordance with ACMG guidelines.ResultsGVs were identified in 12 of 191 patients (6.3%), affecting 7 different genes: ZNRF3, ARMC5, APC, CACNA1H, SCNN1B, PDE11A, and KCNJ5. Most of the detected variants were classified as variants of uncertain significance (VUS). Genotype-phenotype analysis revealed that some patients with GVs had bilateral adrenal lesions and/or mild autonomous cortisol secretion (MACS). No variants were classified as clearly pathogenic.ConclusionThis study provides new insights into the germline genetic landscape of adrenal incidentalomas. Although GVs were identified in a minority of patients, their clinical significance remains unclear due to the predominance of VUS. These findings do not currently support widespread germline testing in routine clinical management of adrenal incidentalomas. Nevertheless, the detection of potentially pathogenic variants may inform future studies exploring their possible role in adrenal tumorigenesis.